Integrasi Kurikulum Pesantren dalam Mengembangkan Nalar Kritis Siswa Pada Sekolah Menengah Pertama - Ridwan, Mujib (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2025)
This research aims to find findings from the substance of curriculum integration between formal institutions, in this case schools and Islamic boarding schools, related to the development of students' critical thinking skills. This research uses a disciplinary approach to qualitative field research (Field Research) which is carried out using a descriptive analytical approach. The application in the research process is to obtain comprehensive data, maintain the relevance of the data to the research objectives using three methods, namely observation, interviews and documentation. The results of the research show that there has been an increase in the development of critical reasoning at SMP Plus Al Hadi Tuban students during the process of teaching and learning activities both in class and outside of class due to efforts to integrate the curriculum. Curriculum integration by combining every aspect of learning content in full collaboration provides good progress for identifying students' critical thinking patterns